C11, a novel ﬁbroblast growth factor receptor 1 (FGFR1) inhibitor, suppresses breast cancer metastasis and angiogenesis - Chen Zhuo; Tong Lin-jiang; Tang Bai-you; Liu Hong-yan; Wang Xin; Zhang Tao; Cao Xian-wen; Chen Yi; Li Hong-lin; Qian Xu-hong; Xu Yu-fang; Xie Hua; et al. (Acta Pharmacologica Sinica; Vol 40, No 6 (June 2019): Acta Pharmacologica Sinica, 2019)
The ﬁbroblast growth factor receptors (FGFRs) are increasingly considered attractive targets for therapeutic cancer intervention due to their roles in tumor metastasis and angiogenesis. Here, we identiﬁed a new selective FGFR inhibitor, C11, and assessed its antitumor activities. C11 was a selective FGFR1 inhibitor with an IC50 of 19 nM among a panel of 20 tyrosine kinases. C11 inhibited cell proliferation in various tumors, particularly bladder cancer and breast cancer. C11 also inhibited breast cancer MDA-MB-231 cell migration and invasion via suppression of FGFR1 phosphorylation and its downstream signaling pathway. Suppression of matrix metalloproteinases 2/9 (MMP2/9) was associated with the anti-motility activity of C11. Furthermore, the anti-angiogenesis activity of C11 was veriﬁed in endothelial cells and chicken chorioallantoic membranes (CAMs). C11 inhibited the migration and tube formation of HMEC-1 endothelial cells and inhibited angiogenesis in a CAM assay. In sum, C11 is a novel selective FGFR1 inhibitor that exhibits potent activity against breast cancer metastasis and angiogenesis.